1999
DOI: 10.1038/sj.gt.3300796
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plasma cholesterol lowering effect of retrovirus-mediated LDL receptor gene transfer to WHHL rabbit liver after improved surgical technique and stimulation of hepatocyte proliferation by combined partial liver resection and thymidine kinase– ganciclovir treatment

Abstract: In this study we report an improved method for in vivo gene A 50% decrease was also observed in plasma triglycertransfer to liver. Repeated injections of Moloney murine ides. Liver function tests indicated a transient increase in leukemia virus-derived retroviruses containing LDL recepplasma alkaline phosphatase level up to 12 weeks after tor cDNA were given to the portal vein in combination with the gene transfer. In situ PCR and RT-PCR analyses india 10% partial liver resection and stimulation of hepatocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…A clinically applicable repopulation method to induce cell damage is surgical manipulation of liver tissue [10][11][12]. Removal or permanent blood vessel ligation of one or more liver lobes induces cell proliferation and restoration of the original cell mass from the remaining liver [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A clinically applicable repopulation method to induce cell damage is surgical manipulation of liver tissue [10][11][12]. Removal or permanent blood vessel ligation of one or more liver lobes induces cell proliferation and restoration of the original cell mass from the remaining liver [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with homozygous familial hypercholesterolemia lack functional LDL receptors and develop high plasma cholesterol levels leading to severe atherosclerosis and coronary heart disease during the first or second decade of life. One strategy besides the conventional therapy would be to restore the LDL receptor activity by transferring the functional LDL receptors into hepatocytes and thus lower the plasma cholesterol level [20,21]. The feasibility of this approach has been demonstrated in animal models with in vivo and ex vivo methods [20] and the results of the first clinical trial have also been reported.…”
Section: Hyperlipidemia and Atherogenesismentioning
confidence: 97%
“…One strategy besides the conventional therapy would be to restore the LDL receptor activity by transferring the functional LDL receptors into hepatocytes and thus lower the plasma cholesterol level [20,21]. The feasibility of this approach has been demonstrated in animal models with in vivo and ex vivo methods [20] and the results of the first clinical trial have also been reported. With retrovirus-mediated, LDL receptor ex vivo gene therapy a 6% to 23% reduction in plasma LDL levels was achieved in three of the five treated patients [21].…”
Section: Hyperlipidemia and Atherogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…In a retrovirus-mediated in vivo study with Watannabe heritable hyperlipidemic (WHHL) rabbits, HSV thymidine kinase was used to induce hepatocyte proliferation with a minimal liver resection. A 20% decline of total cholesterol was present one year later [6].…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%